ANALISIS PENGARUH KUALITAS LAYANAN DAN CITRA TOKO TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING (STUDI PADA KONSUMEN INDOMARET DI SEMARANG) - Anindito, Ronaldo; Idris, Idris (Diponegoro Journal of Management, 2020)
his research was conducted to discover the influence of service quality and store image to customer loyalty through customer satisfaction at Indomaret in Semarang. The population was Indomaretâ€™s customers in Semarang, and the sample criteria was those who ever shopped more than twice at Indomaret. Total samples used were up to 130 respondents which collected using Purposive Sampling Method. The method of data collection was through questionnaire and scientific study. This research utilized Structural Equation Modeling (SEM) for analysis technique and AMOS 23.0 for the analysis tool.Â The result of this research indicated that both service quality and store image had positive significant influence to customer satisfaction and customer loyalty, yet customer satisfaction had positive insignificant influence to customer loyalty.